Investigation of the efficiency of labour safety means by statistical games - Čyras, Petras; Vakrinienė, Sigutė (Journal of Civil Engineering and Management, 2002)
Statistical data regarding causes and number of accidents in enterprises and organisations allow to foresee the average number of traumas for a definite period when no additional means for trauma prevention have been provided. The trauma prevention means differ because they require different financing and decreasing the number of traumas. The suggested mathematical methods give the possibility to appraise the means of trauma prevention according to the definite sum invested. Some accidents are related to individual miss-steps/mistakes at work. Trying to find out the ways for optimal trauma prevention we can take the latter causes as statistical game of “nature” state and certain possible situations of existing in determination. They are impossible to be changed, though some preventive means applied by employees may decrease the trauma cases caused by individual safe control violation. As soon as the optimal strategy of the aforementioned matrix game is found, the most important preventive means could be determined. They could guarantee the real decrease of the trauma cases in spite of any violations by employees. A certain modification of the straightforward programme making task allows us to get an optimal allocation of means necessary for trauma prevention, thus evaluating the effectiveness of preventive measures when the optimal financing is found as the means are increasing. Frist Published Online: 30 Jul 2012